From the Newspaper serial to the novel (1853-1863): mediation of the periodical press in the Foundation of Alberto Blest Gana's narrative project - Pas, Hernán (2021)
Scholarly studies on Alberto Blest Gana have generally disregarded the author's production prior to his narrative cycle, begun with his novel La aritmética en el amor (Arithmetic in Love) (1860), awarded first prize in a literary contest sponsored by the Universidad de Chile. Nonetheless, the canonical cycle of his first narrative period (which includes his famous Martín Rivas and El ideal de un calavera) shares with his earlier fiction the fact that the novels were originally published in the press. Indeed, with the exception of the award-winning novel and Juan de Aria - published in the Aguinaldo of the newspaper El Ferrocarril - all the author's production from his first narrative period was published in periodical publications, decisive in consolidating his narrative project. This essay analyses the mediation of the periodical press (and its subgenres, such as the folletín (newspaper serial) and the artículo de costumbres (a literary vignette of customs)) in the foundation of Blest Gana's narrative scheme, contemplating the diversity of his production. The main features of his project were embodied, materially speaking, in the space of the folletín. It was in this space, in short, where the author's narrative managed to challenge an extended reading public, necessary for the constitution of a national literature.